MANAGEMENT PLAN FOR RECREATIONAL FISHING IN THE HYDROGRAPHIC ÂNCORA RIVER BASIN - M. V. Martinho, António (2024)
This work is the result of the most recent studies carried out by the ICNF in the drainage basin of the future recreational fishing area (ZPL) of the Âncora river. These supported the design of a plan for the sustainable management and exploitation of recreational fishing in this river basin, which is part of the Minho and Lima Hydrographic Region (RH1). Seven sampling stations were set up for this purpose. Six in the main watercourse and one in the Regueiro dos Enxurros, in the middle of an area of successive waterfalls, just before its confluence with the Regueiro da Lapa Ladrão, which is considered to be the source of the Âncora River. At these stations, hydromorphological quality assessments were carried out on 500 m stretches using the River Habitat Survey (RHS) methodology and fish community monitoring (three per station, for a total of twenty-one inventories) using the electrofishing technique. The results made it possible to consider implementing more sustainable management and exploitation measures for fishing in these continental bodies of water. In this context, the management options took marked account of conservation objectives associated with the presence of European eels (Anguilla anguilla) and red eels (Achondrostoma spp.), the wide distribution of trout (Salmo trutta) and the reduced presence of boga (Pseudochondrostoma duriense) whose distribution in the upper third of this drainage basin is conditioned by a very peculiar geomorphology, filled with numerous slopes, which give rise to beautiful waterfalls. With the information collected, data on the age, growth and physical condition of the ichthyofauna assessed was studied, and their relationship with the different types of habitat in which they occurred was established. The results show that these are watercourses with "Excellent" quality habitats, but with levels of artificialization ranging from "severely modified" to "predominantly unmodified", the result of anthropogenic actions over time. Trout (Salmo trutta) are the most widely distributed species along the main watercourse. The absence of exotic aquaculture species in the samples and the lack of medium to large water impoundment structures in the hydrographic network evaluated should be emphasized. The existing river compartmentalization is materialized by the numerous micro-weirs (many of which allow aquatic organisms to migrate for a good part of the year) and a few waterfalls (natural cascades) that prevent fish from passing through. The trout show isometric growth for all the sampling stations, a balanced physical robustness and a maximum lifespan of 6 years. As a practical result of this study, a Recreational Fishing Management and Exploration Plan for the Âncora River will be created, which will support the design of measures to promote the sustainable management of recreational fishing in the area of the future LPZ, reconciling this activity with nature conservation objectives.